Language of web: bynet discourse and Belarusian netspeak - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2022)
It is proved that the modern Internet space creates a fundamentally new communication environment (social networks, chats, etc.), the capabilities of which, in turn, act as a trigger for linguistic transformations. It is the language of Internet communications that is today the field where new trends in language development are most actively formed. The functioning of the language in the network gives rise to a number of new phenomena. So, Internet discourse gives rise to such phenomena as massive abbreviations and an abundance of neologisms (including game ones), acronyms and backronyms, syngrahemics and supragrahemics, interlanguage hybrids, new tools for expressing subject-subject relations (formulas of politeness, for example) and many others. This poses new problems for both linguistics and philosophy of language. For example, it is shown that in the context of Internet communications, the classic dichotomy of verbal speech and written forms of language is blurred: on the one hand, in chats and forums, the language is formally represented by written texts, on the other – interactive dialogues actually set living one-time communication, which allows one to speak simultaneously, interrupt the interlocutor, respond immediately, etc., and all these are characteristic of verbal speech. It is concluded that if until now the main presenter of language in culture has clearly been fiction as embodying the established norm of the correct language, then today language practices (usus) come to the fore, reflecting the trends of linguistic evolution that are forming in the present continuous, that sets a new accentuation in modern culture, namely the prevalence of descriptive linguistics over prescriptive.
Keywords: Internet communication; web language; written language; verbal speech; language corpus; abbreviations; neologisms; acronyms; backronyms; syngrahemics; supragrahemics; interlanguage hybrids; literary norm; linguistic usus; representation of language in culture